Researches on Crack Propagation of the Two Filled Noncoalescent Coplanar Flaws under the High Strain Rate Loading by means of AUTODYN-Based Simulation - Guangming Zhao; Chongyan Liu; Cheng Pan; Xiangrui Meng (Geofluids)
To study the influence of fillings on rock failure. By turning to the Drucker-Prager strength model and cumulative damage criteria, investigations are made, with the nonlinear AUTODYN software, into crack propagation behaviors in crack-filled and unfilled specimens under uniaxial dynamic loading. Under investigations are crack initiation position, sequence and angle, and coalescence mode. According to the mode of propagation and coalescence, cracks are divided into three types, i.e., the tensile wing, the antiwing, and the horsetail. The simulation results show that under uniaxial dynamic loading, differences are found in initiation position, angle, and coalescence mode for specimens with cracks filled or otherwise. However, filling does not affect crack initiation sequence. Under the same loading, the damage to filled specimen is less severe than that to the unfilled specimen.